2018
DOI: 10.1016/j.exger.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetically elevated gamma-glutamyltransferase and Alzheimer's disease

Abstract: Observational epidemiological evidence supports a linear and independent association between serum gamma-glutamyltransferase (GGT) concentrations and the risk of Alzheimer's disease (AD). However, the causality of this association has not been previously investigated. We sought to assess the causal nature of this association using a Mendelian randomization (MR) approach. Using inverse-variance weighted MR analysis, we assessed the association between GGT and AD using summary statistics for single nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
3
1
1
Order By: Relevance
“…A study of GGT and Parkinson's disease is also consistent with our finding, that GGT may contribute to neurodegenerative disease in the female population (Yoo et al, 2020 ). However, contrary to our findings, a genetic study found no clear link between GGT and cognitive function (Kunutsor et al, 2018 ), possibly because that study did not include a subgroup analysis based on sex, which is essential because of the finding from previous study that estrogen may affect GGT activity in the body (Zarida et al, 1994 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A study of GGT and Parkinson's disease is also consistent with our finding, that GGT may contribute to neurodegenerative disease in the female population (Yoo et al, 2020 ). However, contrary to our findings, a genetic study found no clear link between GGT and cognitive function (Kunutsor et al, 2018 ), possibly because that study did not include a subgroup analysis based on sex, which is essential because of the finding from previous study that estrogen may affect GGT activity in the body (Zarida et al, 1994 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Since we performed a cross-sectional study, we could not refute the conclusion reached in previous studies that there is no causal link between GGT and MCI (Kunutsor et al, 2018 ). However, there has been no previous research into the relationship between GGT and cognitive function in the female population, so our results are significant in terms of the diagnosis and early indication of MCI in the female population.…”
Section: Limitationsmentioning
confidence: 74%
See 1 more Smart Citation
“…The risk was highest in the group with a high baseline GGT level and highest GGT variability (27.3%) [73] . Consistently, another recent study conducted on 2943 Chinese women showed that the prevalence of mild cognitive impairment increased from 8.4% among women in the first GGT tertile to 21.4% among women in the fourth GGT quartile with a higher prevalence in the presence of obesity, sleep deprivation, hyperuricemia, or menopause [74] .…”
Section: Ggt Neurodegenerative Disorders and Dementiasupporting
confidence: 67%
“…Gamma Glutamyl Transferase merupakan penanda cedera hati dan konsumsi alkohol yang berlebihan (Kunutsor et al, 2018). Pemeriksaan GGT seringkali diukur bersamaan dengan pemeriksaan enzim lainnya seperti ALP, jika kadar GGT atau ALP meningkat, diduga terjadi gangguan pada hati ataupun saluran empedu (Rosida, Berdasarkan Tabel 3 diperoleh aktivitas GGT meningkat pada pemain game online sebanyak 57,1% (4 orang) dengan rerata kadar GGT yaitu 25,4 ± 23,4 berdasarkan usia 19-22 tahun.…”
unclassified